Digital Disruption at Field Level: Tipping Point Experiments from Rice Sector - Shaik N. Meera, S. Arun Kumar, Praveen Rapakaand S.R. Voleti (Indian Journal of Extension Education, 2023)
Future Extension and Advisory Services (EAS) across the globe need to innovate and strategize the use of disruptive technologies such as mobile/cloud computing, Internet of Things, big data analytics, locationbased social networks, blockchain technologies etc. Use of digital technologies in rural advisories has been documented well in past two decades, but there has been no cross learning between organizations, extension organizations, value chain stakeholders and farmers. The paper presents results from a series of tipping point pilot experiements conducted in Indian rice industry and probable scalingup options. In these experiments, value chain players and farmers were involved with randomised control trials and primary surveys. Randomised Control Trials (RCTs) were conducted in Southern provinces in India involving farmers and data were analyzed with one way ANOVA. For value chain players, a series of survey based experiments are conducted. The yield gains in T1 (Digital extension interventions and social media) were significantly higher compared to T2, T3 and Control (.034, .041, .002) at 5 per cent level of significance. Similar analytics are done in entire supply chain management in Indian rice industry that helps shaping future extension advisory systems specific to Asian & African rice industry. These experiments suggest that rice industry can realize disruptive innovations in extension delivery with the help of big data analytics for mapping inputs supply and marketing, location based services for resource tracking & dynamic distribution, virtual pooling for higher market prices, weather fore-warning, proximity-based notification (push or pull) of advisories and targeted advertising.